A Semiotic-Interpretive Approach to Digital Discourse: “Exiting the Body’s Inscription” by Mounam Al-Azraq as a Case Study - bendahoua, khaira (El Omda in Linguistics and Discourse Analysis, 2022)
This article provides a semiotic approach, to a composite poetic discourse, combining verbal, digital, musical, and artistic discourse, in general, a speech of all that we can say, is a dodgy tool for the monetary mechanism. That inevitably stands helpless, but this rhetorical intensification, and because there is no criticism or digital reading of the digital text, the possibility of this type of speech being influenced and powered by the recipient is determined by the choices of the critical recipient or reader. That's why we chose to read the first composite.